Cognition in context New insights into language, culture and the mind - Bogucki, Lukasz; Bogucki, Lukasz (Peter Lang, 2019)
As cognitive scientists continue to probe into the nature of the human mind, it is increasingly clear that research into cognition cannot be dissociated from the context in which our mental activity occurs. The papers collected in this book testify to the growing interest in adopting a broad characterisation of what counts as relevant context. The vices of seeking essences behind complex phenomena should not go unnoticed, the primary, and possibly the most crucial, downside of this approach being a reductionist treatment of the human mind. With this book, the authors want to show that humans are not merely brains, minds, speakers, learners, readers, etc., but, first and foremost, complex beings who communicate within and beyond the contexts of their own cultures.